Reviewer acknowledgement 2012 - Belizán José M (BMC, 2013)
Contributing reviewers The editor of Reproductive Health would like to thank all our reviewers who have contributed to the journal in Volume 9 (2012). Peer review is essential to the reliable communication of science and we appreciate the effort and generosity of our reviewers who give their time to furthering the excellence and integrity of the journal.